2005
DOI: 10.1002/abc.114
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Campus Responsibility for the Writing Assessment Process

Abstract: The Writing Across the Curriculum movement sensitized institutions to the need for institutionwide commitment to improving student writing. At the University of South Florida, a widely used rubric has offered a powerful method for moving from spoken commitment to real change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The reviewed evidence supports the need for a comprehensive and deliberate approach to teaching writing to students (Cowles et al, 2001;Flateby, 2005;Harris, 2006;Luthy et al, 2009;Whitehead, 2002). While the overall approach, model, or framework for facilitating writer development varies, a consistent set of strategies have been reported in the published literature.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The reviewed evidence supports the need for a comprehensive and deliberate approach to teaching writing to students (Cowles et al, 2001;Flateby, 2005;Harris, 2006;Luthy et al, 2009;Whitehead, 2002). While the overall approach, model, or framework for facilitating writer development varies, a consistent set of strategies have been reported in the published literature.…”
Section: Discussionmentioning
confidence: 84%
“…While the overall approach, model, or framework for facilitating writer development varies, a consistent set of strategies have been reported in the published literature. Using Bloom's Taxonomy (Flateby, 2005;Granello, 2001;Harris, 2006), to create sequenced assignments (Harris, 2006;Luthy et al, 2009) that are peer and/or faculty reviewed and then revised (Caffarella & Barnett, 2000;Harris, 2006;Luthy et al, 2009;Rieber, 2006), and evaluated or assessed using a detailed rubric (Harris, 2006;Luthy et al, 2009) are the most frequently addressed strategies reported in the research and best practices literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Faculty members across disciplines such as math, sciences, business, and the arts that incorporate writing into their core requirements are often challenged by students' resistance to writing; resistance which may stem from anxiety, poor academic performance, and lack of recognition that writing is important in their lives. Flateby (2005) argued that the entire campus community must participate in the assessment process to improve the quality of students' writing. One small, four-year university on the United States-Mexico border participated in the assessment process by implementing the Quality Enhancement Plan, which was focused on assessment and enhancement of college students' writing performance.…”
Section: Christy Teranishi Martinez | Ned Kock | Jeffrey Cassmentioning
confidence: 99%